Al2O3-Ge-On-insulator n- and p-MOSFETs with fully NiSi and NiGe dual gates - Yu, DS; Huang, CH; Chin, A; Zhu, CX; Li, MF; Cho, BJ; Kwong, DL (My University, 2004)
High-kappa, A1(2)O(3)/Ge-on-insulator (GOI) n- and p-MOSFETs with fully silicided NiSi and germanided NiGe dual gates were fabricated. At 1.7-nm equivalent-oxide-thickness (EOT), the A1(2)O(3)-GOI with metal-like NiSi and NiGe gates has comparable gate leakage current with A1(2)O(3)-Si MOSFETs. Additionally, A1(2) O-3-GOI C-MOSFETs with fully NiSi and NiGe gates show 1.94 and 1.98 times higher electron and hole mobility, respectively, than A1(2)O(3)-Si devices, because the electron and hole effective masses of Ge are lower than those of Si. The process with maximum 500 degreesC rapid thermal annealing (RTA) is ideal for integrating metallic gates with high-kappa to minimize interfacial reactions and crystallization of the high-kappa material, and oxygen penetration in high-kappa MOSFETs.
Keywords: Ge; Ge-on-insulator (GOI); MOSFET; NiGe; NiSi